2016
DOI: 10.1515/aoter-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Review of numerical models of cavitating flows with the use of the homogeneous approach

Abstract: The focus of research works on cavitation has changed since the 1960s; the behaviour of a single bubble is no more the area of interest for most scientists. Its place was taken by the cavitating flow considered as a whole. Many numerical models of cavitating flows came into being within the space of the last fifty years. They can be divided into two groups: multifluid and homogeneous (i.e., single-fluid) models. The group of homogenous models contains two subgroups: models based on transport equation and press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 25 publications
(29 reference statements)
0
20
0
2
Order By: Relevance
“…Source terms in the transport equation for the volume fraction are modeled, considering the evaporation and condensation processes. Niedzwiedzka et al (2016) gave a detailed overview of the available models that can be used with homogenous approach. These models are generally validated with hydrofoil, venturi, or cylinder test cases.…”
Section: Introductionmentioning
confidence: 99%
“…Source terms in the transport equation for the volume fraction are modeled, considering the evaporation and condensation processes. Niedzwiedzka et al (2016) gave a detailed overview of the available models that can be used with homogenous approach. These models are generally validated with hydrofoil, venturi, or cylinder test cases.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of models, the phasechange rate is controlled using a source term which is typically derived from the Rayleigh-Plesset (R-P) equation, as shown in [9][10][11][12]. A detailed review of such models can be found in [13,14]. The single-fluid approach for modelling cavitation uses an equation of state (EoS), which relates density and speed of sound with pressure and temperature.…”
mentioning
confidence: 99%
“…On the other hand, the TEM incorporate a transport equation for the mass and volume fraction that regulates the mass transfer between the two phases. The transport equation is usually based on a simplified version of the main equation of bubble dynamics, the Rayleigh-Plesset equation, which relates bubble growth with the internal bubble pressure conditions [24]. A great number of models have been proposed in order to describe the net mass transfer between the liquid and vapour phase at the bubble interface.…”
Section: Introductionmentioning
confidence: 99%